Nutrition Class Intervention Through Emotional Demonstration Approach to Underweight Toddler Nutritional Status During the Covid_19 Pandemic in West Lombok Regency: Intervensi Kelas Gizi Metode Emo Demo terhadap Status Gizi Balita Underweight Pada Masa Pandemi Covid-19 di Kabupaten Lombok Barat - Baiq Dewi Sukma Septiani; Lalu Dwi Satria Ardiansyah (Universitas Airlangga, 2022)
Background: One of Covid-19 impacts was the lowering community economic level. This phenomenon affected the ability of purchasing better food. SSGI Data (2021), presented that 22.4% of toddlers in the NTB Province were categorized underweight. West Lombok Regency were the first rank from tenth regencies in NTB for underweight prevalence toddlers (20,26%). Underweight were caused by inadequate breastfeeding, erroneous of MP-ASI given, and several infectious desease. Purpose: This study aimed to determinee the effect of emo-demo nutritional education on thee underweight toddler’s nutrition status during the Covid-19 pandemic in West Lombok Regency. Methods: This quantitative research was a Quasi-Experimental with Pre-Post Control Design. This research was conducted from June to August 2022. The total sample were 32 people whom divided into control and experiment groups based on inclusion criteria; toddlers aged 6-59 months, underweight toddlers cared by their mothers, Respondents were from Batu Kuta Village, West Lombok Regency Purposive sampling were used to gather the data. Data were analyzed using paired sample t test and multiple linear regression. Results: The results showed that the underweight toddler’s nutrition status gained after nutritional class intervention using emo-demo method. There were 68.8% of toddlers with heavy weight based on the BB/U index (p=0.000), 87.5% of toddlers with normal weight based on the TB/U index (p=0.000) and 75% of toddlers with fair based on nutritional status nutrition index BB/TB (p=0.686). Conclusion: The nutrition class intervention gained the nutritional status of underweight toddlers based on the BB/U and TB/U indices during the Covid-19 pandemic in West Lombok Regency.